Persepsi Pengunjung Terhadap Sapta Pesona Objek Wisata Pantai Pohon Seribu Sasak Ranah Pasisie Kabupaten Pasaman Barat - Yosrianti Yosrianti; Dasrizal Dasrizal; Rika Despica (Journal on Education, 2023)
This research was motivated by the lack of application of Sapta Pesona at the Tree Seribu Sasak Ranah Pasisie beach tourist attraction, starting from the problem of beach cleanliness on the beach, which originates from household waste from the people who live along the beach and also waste originating from the sea. waste disposal in the form of salt water resulting from salting salted fish which is dumped on the beach by people who work as salted fish makers which causes a foul smell on the beach, the rise of buskers around the beach which reduces the feeling of safety and comfort for visitors to enjoy the beach, and related facilities and infrastructure such as a lack of public toilets and unavailable parking lots.The type of research used is mixed methods research. This research is a research step that combines two previously existing forms of research, namely qualitative research and quantitative research. The population in this study were all visitors to the Tree Seribu Sasak Ranah Pasisie Beach tourist attraction. Meanwhile, the sample was visitors who happened to meet the researcher at the research site or what is known as incidental sampling.Based on the results of research, visitors' perceptions of Sapta Pesona at the Seribu Beach tourist attraction are quite good with an overall score of 55.48% consisting of visitors' understanding of the Sapta Pesona at the Seribu Beach tourist attraction which was obtained at 54.94% with quite good results, knowledge visitors regarding the application of Sapta Pesona in a tourism destination area or with an average category of quite good with a figure of 55.14% and the attention of visitors to Sapta Pesona in the tourist attraction of the Pulau Seribu Sasak beach in the Pasisie realm is already in the quite good category with percentage 56.37%. The three results of this research are proven from the results of the frequency distribution of the percentage of respondents' answers